Gender Training - Ferguson, Lucy. author. aut Link
XI, 117 p. 4 illus.
Keywords: This book explores develops a case for feminist gender training as a catalyst for disjuncture, rupture and change. Chapter 1 traces the historical development and current contours of the field of gender training. In Chapter 2, the key critiques of gender training are substantively engaged with from the perspective of reflexive practice, highlighting the need to work strategically within existing constraints. Questions of transformative change are addressed in Chapter 3, which reviews feminist approaches to change and how these can be applied to enhance the impact of gender training. Chapter 4 considers the theory and practice of feminist pedagogies in gender training. In the final chapter, new avenues for gender training are explored: working with privilege; engaging with applied theatre; and mindfulness/meditation. The study takes gender training beyond its often technocratic form towards a creative, liberating process with the potential to evoke tangible, lasting transformation for gender equality.